STATISTICAL ANALYSIS OF THE QUALITY OF SERVICE IN THE INTERCANTONAL TERMI-NAL OF THE CITY OF RIOBAMBA - Londo Yachambáy, Fabián (2020)
Customer service is one of the main factors that affect the quality of service in both public and private companies, such is the case of human conglomerates where people or users come to require a service, in our research we try to know the attention To the user that is provided in the intercantonal terminal of the city of Riobamba by the drivers and administrative staff to determine this, a survey was carried out in the field with the main actors and through exploratory statistics determine the benefits and flaws that the terminal has with the purpose of obtaining indicators that help the authorities in charge make decisions that go towards continuous improvement.